Investigating Customer Satisfaction on “Whoosh” High-Speed Train Services Using Importance Performance Analysis and Customer Satisfaction Index - Achmadi, Rudhi; Widiarto, Setyo (Cita Konsultindo Research Center, 2025)
This study aims to determine the level of satisfaction of Whoosh high-speed train service customers with the services provided by KCIC management. The